A Rate Dependent Stress-Strain Relationship Model for Normal, High and Ultra-High Strength Concrete. Issue 3 (September 2013) - Ngo, Tuan; Mendis, Priyan; Whittaker, Andrew
High and ultra-high strength concrete are becoming popular for many applications, including critical infrastructure subjected to high strain rate loading such as blast and impact. A strain rate dependent material model that is applicable to a range of strengths, varying from normal strength to ultra-high strength concrete, is presented in this paper. The results from a comprehensive experimental study conducted to investigate the strength and deformation capacity of concrete cylinders under high-velocity impact loading using a Split Hopkinson Pressure Bar (SHPB) test setup is reported. Unconfined 50 mm diameter concrete cylinders with compressive strengths varying from 32 MPa (4640 psi) to 160 MPa (23 200 psi) were tested to derive the dynamic properties of concrete at strain rates up to 300 s −1 . The SHPB test data were analysed to obtain the stress-strain relationships and strength dynamic increase factors (DIFs) for these concrete specimens under dynamic axial compression.